2009
DOI: 10.1111/j.1540-6210.2009.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Policy Process: The Work of Henry Mintzberg

Abstract: Do Henry Mintzberg's writings make an enduring, invaluable contribution to our understanding of the contemporary public policy process? Mintzberg argues that organizations display eight structural configurations and corresponding coordinating mechanisms. Such structural configurations are shaped by a variety of contingency factors, especially power and environmental ones. Using Mintzberg's work, eight policy modes, corresponding to structural configurations within government organizations and political systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
0
17
0
3
Order By: Relevance
“…The espoused values, which are the artificial variables created to support the strategy of the organization, serve as the guiding principles and standards of conduct for a company's employees. By implementing espoused values in the organization, managers are trying to establish what Mintzberg calls the standardization of norms (Matheson, 2009) so that everybody in the organization would be performing their tasks according to the same set of beliefs. Of course, this process will not work if managers try to implement the values that mismatch with the ones that employees already have.…”
Section: Values and Their Fitmentioning
confidence: 99%
“…The espoused values, which are the artificial variables created to support the strategy of the organization, serve as the guiding principles and standards of conduct for a company's employees. By implementing espoused values in the organization, managers are trying to establish what Mintzberg calls the standardization of norms (Matheson, 2009) so that everybody in the organization would be performing their tasks according to the same set of beliefs. Of course, this process will not work if managers try to implement the values that mismatch with the ones that employees already have.…”
Section: Values and Their Fitmentioning
confidence: 99%
“…Hood [40] suggested that targets are more likely to be achieved in a hierarchical and centralized context. Mintzberg [41][42][43] also advocated that in centralized organizations a top-down planning with explicit targets can facilitate organizational performance [44].…”
Section: Discussionmentioning
confidence: 99%
“…También, Mintzberg (1996) refleja este carácter multidisciplinar en nueve parámetros de diseño referidos al esquema de puestos de trabajo (la especialización, la formalización del comportamiento, la preparación y el adoctrinamiento), al diseño de la superestructura (agrupación de unidades y tamaño de la unidad), al diseño de vínculos laterales (sistemas de planificación y control, y dispositivos de enlace) y diseño del sistema decisor (centralización). Lo cierto, es que se exalta la afirmación de Matheson (2009) sobre que la formalización del comportamiento y la centralización son los parámetros de diseño clave de la estructura.…”
Section: * Nota De Agradecimiento: Este Artículo Versa En Un Proyectounclassified
“…En este ámbito, resaltan los trabajos de Burns y Stalker (1961), quienes distinguen estructuras mecanicistas y orgánicas; Mintzberg (1996) identifica cinco configuraciones estructurales (estructura simple, burocracia maquinal, burocracia profesional, forma divisional y adhocracia), y más recientemente, Matheson (2009) propone ocho configuraciones estructurales (profesional, misionera, maquinal, diversificada, en red, política, autocrática y carismática). Sobre ello y señalando a Burns y Stalker (1961), las estructuras orgánicas son menos formalizadas, más flexibles, más creativas y adaptadas a la innovación.…”
Section: H 2 La Centralización De La Estructura Organizativa Es Mayunclassified